KAJIAN NILAI PENDIDIKAN PADA TRADISI GAMBANG BECERITO DESA LEBUNG PANJANG JAMBI TULO - Melly Kurniati; Harry Soedarto; Priyanto Priyanto (Ensiklopedia of Journal, 2023)
This research is a qualitative research which aims to find out the form of the "Xylophone Becerito" tradition of Lebung Panjang Jambi Tulo Village and describe the educational values contained in the humming tuo of the xylophone Becerito tradition. Research data collection techniques, namely observation techniques, interview techniques and documentation techniques. Then the data obtained were analyzed using content analysis and tested through method triangulation. The results of the study show that the Gambang Becerito tradition contains moral educational values where the values of religious education include gratitude, fear of sinning, praying to God and being sincere.Keywords: Tradition Xylophone Becerito, Educational value, Jambi Tulo